Synthesis and antiproliferative activity of 6, 7-disubstituted-4-phenoxyquinoline derivatives bearing the 2-oxo-4-chloro-1, 2-dihydroquinoline-3-carboxamide moiety. Issue 7 (1st April 2016) - Tang, Qidong; Zhai, Xin; Tu, Yayi; Wang, Ping; Wang, Linxiao; Wu, Chunjiang; Wang, Wenhui; Xie, Hongbo; Gong, Ping; Zheng, Pengwu
Graphical abstract: Abstract: A series of 6, 7-disubstituted-4-phenoxyquinoline derivatives bearing the 2-oxo-4-chloro-1, 2-dihydroquinoline-3-carboxamide moiety were synthesized, and evaluated for their antiproliferative activity against 5 cancer cell lines (H460, HT-29, MKN-45, A549, and U87MG). Most compounds showed moderate to excellent potency, and compared to foretinib, the most promising analog42 (c-Met/Flt-3 IC50  = 1.21/2.15 nM) showed a 6.1-fold increase in activity against H460 cell line in vitro. The enzymatic assays (c-Met, VEGFR-2, Flt-3, PDGFR-β, c-Kit, and EGFR) of compound42 were evaluated in vitro. Docking analysis showed that compound42 could form three hydrogen bonds with c-Met. Structure–activity relationship studies indicated that a more water-soluble cyclic tertiary amine and electron-withdrawing groups at 4-position of the phenyl ring contribute to the antitumour activity.